Physiological superiority of millet crops for climate resilience - Srividhya, S; Swarna, R; Nayak, D Seva (Indian Farming, 2023)
Millets are the most important category of grain crops. They are a group of small-seeded grasses that are highly tolerant to environmental stresses and have high physiological efficiency. They are an important food security crop in many parts of the world, especially in Africa and Asia. Millets have several key adaptive traits that make them well-suited for climate resilience, including their short growing season, deep root system and ability to tolerate high temperatures and drought conditions. The importance of these crops in terms of their physiological and anatomical make up is highlighted in this article, which needs to be utilized for selection of superior and high yielding germplasm for competing the yield potential of other major cereals.